IMPROVE LEARNING OUTCOMES ON THE THEME OF RESPONDING TO TECHNOLOGICAL DEVELOPMENTS THROUGH THE APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) LEARNING MODEL - Kristina, Marilin; Dewi, Novi Ayu Kristiana (STMIK Pringsewu, 2023)
This study aims to improve learning to determine the improvement of student learning outcomes on the theme of Responding to the Development of Technology grade III SDN 7 Negerikaton through the Contextual Teaching and Learning learning model. This research is a classroom action research (Classroom Action Research) using a classroom action research model from Kemmis and Mc Taggart, this research was conducted as many as two cycles. Each cycle is held three times, with four stages, namely planning, implementation, observation and reflection. The subjects of this study were all grade III students of SDN 7 Negerikaton for the 2021/2022 academic year with a total of 23 students. Data was collected through observation sheets and tests on each cycle. The results showed that, the average learning outcomes of students increased. The completion percentage has also increased. In the pre-cycle the percentage of completeness was 34.78%, cycle I with a percentage of completeness of 56.52%, while in cycle II with a percentage of completeness of 91.30%. Thus, the Contextual Teaching and Learning learning model can improve the learning outcomes of students in grade III SDN 7 Negerikaton.